FAKTOR-FAKTOR YANG MELATARBELAKANGI PILIHAN RASIONAL INDONESIA TERHADAP "QUADRILATERAL SECURITY DIALOGUE (QUAD)" 2.0 DI KAWASAN INDO-PASIFIK - Nanda Ramadhanti Lesmana (2022)
Rivalry between the United States (US) and Tiongkok in the Indo-Pacific has an impact on stability in the region. The revival of the Quad consisting of the US, Japan, India and Australia in order to create regional strength by bringing together a common goal, which is known as the Indo-Pacific strategy. Geopolitically, the crucial point between the Indo-Pacific subregion is maritime Southeast Asia and especially Indonesia. It is hoped that Indonesia can support the role of the Quad countries in the region. But after review Indonesia itself chose to be absent from the debate about the Quad. The Quad is not part of Indonesia's view of the Indo-Pacific. The preparation of this research is to find out the factors behind the rational choice made by Indonesia towards Quad 2.0 in the Indo-Pacific region. The author uses a qualitative method with primary and secondary data which will then be analyzed using the theory and concept of Rational Choice and Strategic Partnership. The results of this study explain that Indonesia always considers rational choices of various factors including internal and external so as to be able to achieve the national interest to be achieved.